2006
DOI: 10.3892/ijmm.18.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of hyaluronan, CD44, and inflammatory cells in the rat kidney after ischemia/reperfusion injury

Abstract: Ischemia/reperfusion (I/R) injury in the kidney involves hemodynamic and cellular dysfunctions as well as leukocyte infiltration. Functional recovery occurs via cell proliferation and/or migration. To determine the roles of hyaluronan (HA) and its main receptor CD44 in renal postischemic processes, we compared their localization and expression with that of neutrophils, macrophages, and PCNApositive (regenerative) cells as characterized by immunohistochemistry, up to 28 days after I/R in uninephrectomized rats.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 46 publications
2
53
1
Order By: Relevance
“…Both markers were tightly linked to the areas of TI lesions, suggesting a crosstalk between CD44 and HA, and between these markers and the AAN lesions. CD44 has been associated with regenerating cells in the liver and kidney [8,10,12,20,21] but from the results of our study there is no sign that a lack of CD44 might be involved in the poor tubular regeneration.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…Both markers were tightly linked to the areas of TI lesions, suggesting a crosstalk between CD44 and HA, and between these markers and the AAN lesions. CD44 has been associated with regenerating cells in the liver and kidney [8,10,12,20,21] but from the results of our study there is no sign that a lack of CD44 might be involved in the poor tubular regeneration.…”
Section: Discussioncontrasting
confidence: 46%
“…The frequency of CD44 or CD133-positive cells in the interstitial spaces was evaluated by a semi-quantitative analysis as described previously [8]. Briefly, the distribution of positive cells in the interstitium was performed on one section per animal.…”
Section: Cell Countsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, HA has taken part in the process of occurrence, development and fibrosis in different kinds of nephritis and diabetic nephropathy; HA also makes a difference to the pathologic process of renal ischemia-reperfusion injury and kidney tubular crystallization [9][10][11][12] . Many studies have confirmed that HA plays very important roles in the biological process of many kinds of malignancy such as mammary cancer, gastric cancer, colorectal cancer, ovarian cancer, melanoma, glioma, lung cancer, prostatic cancer and head & neck cancer, etc.…”
Section: Discussionmentioning
confidence: 99%